(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
The premarital love stories of Manoj Bose are socially healthy and wholesome. The author explores the extraordinary in the ordinary form of love in these stories mainly set in the village life. There are many different expressions of love in the stories of this stage. Some stories show one loved the other, but was not loved in return. In some stories the two love each other. And in some stories, one is deceived by love. Apart from these three, there are other types of stories at this stage which Manoj Bose has given an opportunity to make a love story completely but has given them a different dimension with wilful negligence. As a result, those stories written in an atmosphere of love ended up being anti-romantic. But above all, as a romantic writer, Manoj Bose wants to spread the reader’s love for life through these stories. So the sweetness of love is magnified in his stories. Complex psychoanalysis has no place there. Instead, some idealistic aspects of love have emerged, such as falling in love without getting love, sacrificing self-happiness for love, surrendering to masculinity ignoring wealth, etc. All in all, Manoj Bose’s premarital love stories have managed to establish a specialty.